Effect of short- and medium-chain fatty acid mixture on polyhydroxyalkanoate production by Pseudomonas strains grown under different culture conditions - Szacherska, Karolina; Moraczewski, Krzysztof; Czaplicki, Sylwester; Oleskowicz-Popiel, Piotr; Mozejko-Ciesielska, Justyna (Frontiers in Bioengineering and Biotechnology, 2022)
Short and medium fatty acids (SMCFAs) derived from the acidogenic anaerobic mixed culture fermentation of acid whey obtained from a crude cheese production line and their synthetic mixture that simulate a real SMCFAs-rich stream was evaluated for polyhydroxyalkanoates (PHAs) production. Three individual Pseudomonas sp. strains showed different capability of growing and producing PHAs in the presence of a synthetic mixture of SMCFAs. Pseudomonas sp. GL06 exhibited the highest SMCFAs tolerance and produced PHAs with the highest productivity (2.7 mg/L·h). Based on these observations, this strain was selected for further investigations on PHAs production in a bioreactor with SMCFAs-rich stream extracted from the effluent. The results showed that PHAs productivity reached up to 4.5 mg/L·h at 24 h of the fermentation together with the ammonium exhaustion in the growth medium. Moreover, the PHA monomeric composition varied with the bacterial strain and the type of the growth medium used. Furthermore, a differential scanning calorimetric and thermogravimetric analysis showed that a short and medium chain length PHA copolymer made of 3-hydroxybutyric, -hexanoic, -octanoic, -decanoic and -dodecanoic has promising properties. The ability of Pseudomonas sp. to produce tailored PHAs copolymers together with the range of possible applications opens new perspectives in the development of PHA bioproduction as a part of an integrated valorization process of SMCFAs derived from waste streams.